Advances in pattern recognition ICAPR 2003 proceedings - Mukherjee Dipti Prasad ed.; International Conference on Advances in Pattern Recognition ICAPR 2003 (10-13 Dec 2003 : Kolkata,India); International conference on advances in pattern recognition ICAPR 2003 Kolkata, India 10-13 Dec 2003 (New Delhi Allied, 2003)
The fifth international conference on Advances in Pattern Recognition forms part of a series which was designed to provide a major platform for representing advanced technologies and interchanging ideas in the fields of pattern recognition and digital signal processing. The excellent collection of papers cover theoretical aspects on computational intelligence and pattern clustering, innovative applications in biomedical image processing, remote sensing and document image analysis.
Keywords: Computer pattern recognition